Detection of Methane Gas Using Absorption Spectroscopy Technique in Non-Dispersive Infrared (NDIR) Region - Ab Latif, Fatin Nur Balqis; Yaacob, Maslina (Evolution in Electrical and Electronic Engineering, 2022)
The number of manufacturing plants is growing every day, resulting in air pollution. Typically, haze is caused by air pollution. This work aims to design a methane gas sensor based on absorption spectroscopy in the non-dispersive infrared (NDIR) region. This starts by determining the range of methane absorption wavenumber at the NDIR region by using Spectralcalc.com® gas cell simulator. From the simulation results, the absorption cross-section of methane is 3.4677 x 10-19 cm2/molecule at wavenumber 2949.8507 cm-1. For validation purposes, a comparison between the previous experimental work and this simulation work shows small percentages of differences which is below 1% differences. Next, an analysis of the pressure effect on the methane absorption cross section was carried out by varying the pressure from 1000 mbar to 1200 mbar. The results indicate that at wavenumber 2940.3909 cm-1 the methane absorption cross section is less dependent on pressure changing. Furthermore, it continues with the analysis of the temperature effect on methane absorption cross sections. Here, the temperature varied from 273.15 K to 333.15 K. The results showed that temperature changes do not affect methane absorption cross sections at wavenumbers of 2940.3909 cm-1. For both analyses, this work used three different wavenumbers and the results showed that the absorption cross section at wavenumber 2940.3909 cm-1 is less pressure and temperature dependent compared to other wavenumbers. To optimize the length of a gas cell for the hazardous level of methane concentration, both simulation and theoretical calculations were carried out by using Spectralcalc.com® gas cell simulator and theoretical formula, respectively. The results from both simulation and theoretical calculations gave almost similar results where the optimized length that needs to detect 50000 ppm of methane gas is 1.600 cm. In conclusion, this work successfully simulates and proposes a methane gas sensor based on the absorption spectroscopy technique in the NDIR region.